<span>9x-4=7-2x <em>/+2x
</em><em />11x-4=7 <em>/+4
</em><em />11x=11 <em>/:11
</em>x=1<em>
</em><em /><em /></span>
3x +2y= 11 ----1
x -2 = -4y ---- 2
Equation 2 times by 3
3x -6 = -12y
Subracting 2-1
3x-6=-12y
3x-11=-2y
Leaving
5=-10y
y= -1/2
Hence
B. is the solution
PS, If you rate this as "Brainiest" that would be most appreciated
Answer: -20
Step-by-step explanation: Using the same expression except positive numbers, 4 x 5 = 20.
In this case, we can use this equation to find the product for the expression
4 x -5.
If 4 x 5 = 20, then 4 times -5 will also equal 20. However, since there is a negative factor in this expression, our answer will be negative causing our answer to be <u>-20.</u>
The answer would be b that is bc you answer is decreasing. As you x increase.